2004
DOI: 10.1161/01.hyp.0000109319.63240.08
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Physical Activity and Blood Pressure Is Modified by Variants in the G-Protein Coupled Receptor 10

Abstract: Abstract-Hypertension is strongly related to cardiovascular disease and all-cause mortality. Exercise reduces blood pressure but the response varies between individuals. The mechanisms by which physical activity energy expenditure (PAEE) modifies blood pressure are not fully defined but include modulation of sympathetic tone. Novel polymorphisms in the G-protein coupled receptor (GPR10) have been linked with high blood pressure. GPR10 may mediate the relationship between PAEE and blood pressure via central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
(26 reference statements)
1
12
2
Order By: Relevance
“…1 However, it is probable that BP, like other complex traits, is a function of interactions between genetic and environmental factors. 26 This may explain why no evidence of association between 11␤HSD1 genetic variability and hypertension has yet been reported in humans, despite evidence to this effect in animals. 15,16 Thus, the successful detection of such genetic effects could depend greatly on the background level of these environment exposures during early development (chronic effects) and at the time of the examination (acute effects).…”
Section: Discussionmentioning
confidence: 99%
“…1 However, it is probable that BP, like other complex traits, is a function of interactions between genetic and environmental factors. 26 This may explain why no evidence of association between 11␤HSD1 genetic variability and hypertension has yet been reported in humans, despite evidence to this effect in animals. 15,16 Thus, the successful detection of such genetic effects could depend greatly on the background level of these environment exposures during early development (chronic effects) and at the time of the examination (acute effects).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 shows the interaction between the G62A variant at the G-protein-coupled receptor 10 (GPR10) gene and the physical activity on blood pressure in 700 middle-aged UK whites; 56 these data indicate that the association between physical activity and blood pressure is dependent on the genotype carried at the G62A locus. In common 'G' allele homozygotes in this study, a strong inverse relationship was observed between physical activity and blood pressure.…”
Section: Gene-drug Interactionsmentioning
confidence: 99%
“…Since one of the most likely mechanisms whereby physical activity leads to a reduction in blood pressure is weight loss, statistical analyses need to be adjusted for body mass index in order to reveal whether there is an independent effect of physical activity on blood pressure. However, only approximately half of the studies have adjusted their results for body mass index [71,77,78,81,[84][85][86][87][88][89]. Other studies adjusted mainly for age alone [67,75,80,90] or used no adjustments at all [54,69,72,73,83].…”
Section: Evidence From Cross-sectional Studiesmentioning
confidence: 99%
“…In addition, inadequate adjustments for confounding factors, especially for obesity and diet, may explain the inconsistent findings as well. However, only approximately half of the studies have adjusted their findings for body mass index [71,77,78,81,84,89]. None of the studies adjusted their results for waist circumference or waist-to-hip ratio.…”
Section: Evidence From Cross-sectional Studiesmentioning
confidence: 99%